Anthropometric comparison of cyclists from different events. Issue 1 (March 1989) - Foley, J P; Bird, S R; White, J A
Abstract : An anthropometric analysis was conducted upon 36 competitive male cyclists (mean age 23.4 years) who had been competing on average for 8.2 years. Cyclists were allocated to one of four groups; sprint, pursuit, road and time trial according to their competitive strengths. The sample included cyclists who were classified as category 1, 2, 3 or professional (British Cycling Federation and Professional Cycling Association). The sprint cyclists were significantly shorter and more mesomorphic than the other three groups (p less than 0.05). The time trialists were the tallest, most ectomorphic group, having the longest legs (p less than 0.01), the highest leg length/height ratio (p less than 0.05) and the greatest bitrochanteric width (p less than 0.05). The pursuit and road cyclists were found to have similar physiques, which were located between those of the sprinters and time trialists. The biomechanical implications of these differences in physique may be related to the high rate of pedal revolutions required by sprinters and the higher gear ratios used by time trialists.